CcRR5 interacts with CcRR14 and CcSnRK2s to regulate the root development in citrus - Zhang, Manman; Wang, Fusheng; Hu, Zhou; Wang, Xiaoli; Yi, Qian; Feng, Jipeng; Zhao, Xiaochun; Zhu, Shiping (Frontiers in Plant Science, 2023)
Response regulator (RR) is an important component of the cytokinin signal transduction system associated with root development and stress resistance in model plants. However, the function of RR gene and the molecular mechanism on regulating the root development in woody plants such as citrus remains unclear. Here, we demonstrate that a member of the type A response regulator, CcRR5 regulates the morphogenesis of root through interacting with CcRR14 and CcSnRK2s in citrus. CcRR5 is mainly expressed in root tips and young leaves. The activity of CcRR5 promoter triggered by CcRR14 was proved with transient expression assay. Seven SnRK2 family members with highly conserved domains were identified in citrus. Among them, CcSnRK2.3, CcSnRK2.6, CcSnRK2.7, CcSnRK2.8 can interact with CcRR5 and CcRR14. Phenotypic analysis of CcRR5 overexpressed transgenic citrus plants indicated that the transcription level of CcRR5 was associated with root length and lateral root numbers. This was also correlated to the expression of root-related genes, and thus confirmed that CcRR5 is involved in the root development. Taken together, the results of this study indicate that CcRR5 is a positive regulator of root growth, and CcRR14 directly regulates the expression of CcRR5. Both CcRR5 and CcRR14 can interact with CcSnRK2s.